Pathways to Recidivism: Do Behavioral Disorders Explain the Gang-Recidivism Relationship during Reentry?. (July 2020) - Wolff, Kevin T.; Baglivio, Michael T.; Limoncelli, Katherine E.; Delisi, Matt
Current scholarship on gang involvement and behavior has focused on several individual and environmental factors believed to drive the use of violence, yet limited research has explored the potentially confounding role of behavioral disorders. Using a sample of youth who completed a long-term residential placement within the Florida Department of Juvenile Justice (FDJJ), this study extends the recent findings of DeLisi et al. to determine whether the presence of a conduct disorder or other behavioral disorder renders the effect of gang involvement on recidivism spurious. Using a series of logistic regression models, behavioral disorders were associated with rearrest, but for males only. Furthermore, behavioral disorders did not render the effect of gang membership on rearrest or readjudication spurious, as the main effect of gang involvement held across all models estimated. Gang-involved adjudicated youth present with myriad mental health, temperamental, and individual risk factors.